Normal Wrist Development in Children and Adolescents: A Geometrical Observational Analysis Based on Plain Radiographs. Issue 9 (October 2020) - Sallam, Asser A.; Briffa, Nikolai; Mahmoud, Samer S.; Imam, Mohamed A.
Abstract : Background: To investigate the geometric development of the wrist in relation to the changes in its ossification pattern. This study will help the treating surgeon to identify early deviations from normal in children with musculoskeletal disorders and provide a template for anatomic reduction after trauma scenarios. Methods: A retrospective multicenter analysis was carried out of radiographs of 896 children (896 posteroanterior and 896 lateral views) with normal wrists from January 1996 till April 2016. We stratified patients into different yearly age groups; these included 16 age groups from 1 to 16 years, and 2 sex groups: males and females. We evaluated, depending on the wrist ossification pattern, the ulnar variance, radial and carpal heights, carpal height ratio, radial inclination, volar tilt, together with radiocarpal, scapholunate, and capitate-lunate angles and scapholunate distance. Results: Our analysis showed that the ulna minus variance predominates in children. Radial height, radial inclination, and radiocarpal angle increase steadily during growth and reach their respective expected values at the beginning of the pubertal growth spurt. The scapholunate and capitolunate angles showed a downward trend with growth till reaching the adult values at puberty. Carpal height increased constantly, whereas the carpal height ratio was similar to that in adults. Volar tilt was not developed until the age of 12 years, when it started to increase gradually to reach the adult values by puberty. Both sexes have similar measurements. Conclusions: Most radiologic parameters showed reproducible anatomic changes till the 12-year-old time-point. After that, there are minimal changes till adulthood. Clinical Relevance: The study findings offer a template of pediatric normal values guiding hand and pediatric surgeons in treatment of children with wrist pathology. Abstract : Supplemental Digital Content is available in the text.